THE USE OF SMART AND ACCURATE TECHNIQUE IN IMPROVING STUDENTS’ ENGAGEMENT AND SPEAKING ABILITY AT SMA 1 BATANG ANAI - Lilisuryani Lilisuryani (English Language Teaching and Research, 2018)
Speaking is one of the important skills among the four skills in teaching English as a Foreign Language (EFL). This is because speaking is fundamental to human communication. Just look at what happen in daily life in terms of how many people involve in speaking as compared to writing. Most of the time people speak more than write. Another reason is that many students equate being able to speak a language as knowing the language and therefore view learning the language as learning how to speak the language. Therefore, in order to strengthen students’ motivation in learning English, it is higly recommended that teachers enhance speaking skill in the classroom. However, there are many problems happen in the classroom when it is time to speak. One of the problem is that the students do not talk or say anything at all in the classroom. They feel really shy about talking in front of other students. Another reason is that the students’ silence may simply because the class activities are boring. To tackle the problem above, it is recommended that the teachers increase students’ engagement because it is an important component in English classroom activities, especially speaking. Engagement serves to encourage the development of English skills through a more active form of student-centered learning. Students’ engagement can also provide the teacher with some confidence that learning takes place during the lesson. Researches show that learning is an active, not a passive process and that students learn best and retain more by actively doing. This paper reports a best practice on the use of smart and accurate technique in improving the students’ engagement and speaking ability at SMA N 1 Batang Anai. This technique was applied to the third year students in the second semester of 2017/2018 academic year. The result shows that by using this technique, the students’ engagement in the classroom was really improving. The students, who used to be silent, scrambled to take turn in speaking. The students who used to be passive tended to involve actively in classroom activities. The students who used to be shy started to talk a lot. As a result, their speaking ability was also improving significantly.Key words: smart and accurate, engagement, speaking ability